Breaking down the tumor immune infiltration within pediatric sarcomas - Weil, Rachel; Loeb, David (Frontiers in Endocrinology, 2023)
Immunotherapies are a promising therapeutic option, yet for a variety of reasons, these treatments have achieved limited success against sarcomas. The immunosuppressive tumor microenvironment (TME) of sarcomas as well as lack of predictive biomarkers, decreased T-cell clonal frequency, and high expression of immunosuppressive infiltrating cells has thus far prevented major success using immunotherapies. By breaking down the TME into its individual components and understanding how the various cell types interact with each other as well as in the context of the complex immune microenvironment, can lead to effective therapeutic immunotherapy treatments, potentially improving outcomes for those with metastatic disease.